2014
DOI: 10.1016/j.abb.2014.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Carbenoxolone induces permeability transition pore opening in rat mitochondria via the translocator protein TSPO and connexin43

Abstract: Ca2+-induced permeability transition pore (mPTP) opening in isolated rat brain mitochondria is promoted through targeting of connexin43. After a threshold Ca2+ load, mitochondrial membrane potential drops and efflux of accumulated Ca2+ from the mitochondrial matrix occurs, indicating the mPTP opening. Specific antibodies were used to assess the role of the translocator protein (18 kDa; TSPO) and connexin43 in swelling of isolated rat liver and brain mitochondria induced by carbenoxolone and the endogenous TSPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…-induced MPT pore opening. The same effect was evidenced using PIGA at micromolar concentration (2.5 lM), accordingly to data obtained using other TSPO reversible ligands [72][73][74].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…-induced MPT pore opening. The same effect was evidenced using PIGA at micromolar concentration (2.5 lM), accordingly to data obtained using other TSPO reversible ligands [72][73][74].…”
Section: Discussionsupporting
confidence: 78%
“…Highly debated data in TSPO literature regards the ability of TSPO ligands to modulate MPT pore [72][73][74][75][76][77][78][79][80]. In the present work, the TSPO ligand modulatory activity on MTP pore functioning was investigated on U87MG cell suspension with digitonin-permeabilized plasmatic membrane at different times.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different classes of TSPO-binding chemicals bind to different regions in the TSPO structure with variable specificity. Nevertheless, these effects were considered to be specific, as it was demonstrated that anti-TSPO antibodies could block the MPT [23] induced by the endogenous TSPO-binding heme precursor protoporphyrin IX [18,54]. However, recent experiments using TSPO À/À cells indicate that the effects of both the endogenous protoporphyrin IX and the synthetic PK11195 and Ro5-4864 TSPO ligands were not mediated through TSPO [52], as shown previously [54], and that the mechanism by which the outer mitochondrial membrane regulates the MPT did not involve TSPO [52].…”
Section: Box 2 the Mptmentioning
confidence: 98%
“…Although a role for TSPO was not discussed in the new model, it remains to be explained how TSPO-binding chemicals could modulate cell death processes. The pharmacological evidence supporting a TSPO link to the MPTP appears well documented [22][23][24][25]. Developments in the field of the MPT were extensively described in a recent review on this topic [26].…”
mentioning
confidence: 97%
“…The existence of the CRAC domain in BAX may promote the protein incorporation into the cholesterol-enriched membrane [19]. The CRAC motif is also found in transmembrane domains of connexin43 (LLIQWYIY), which is present in mitochondria, where it might interact with TSPO [20]. Interestingly, proteins shown to bind cholesterol, e.g., VDAC and TSPO, or having the CRAC motif, e.g., TSPO and Bax, participate in the regulation of permeability of the outer mitochondrial membrane.…”
Section: Introductionmentioning
confidence: 99%